Minority Rights and Democratic Consensus: The Irish Same-Sex Marriage Referendum - Doyle, Oran (My University, 2020)
In 2015, Ireland became the first country in the world to introduce same-sex marriage by popular referendum. In just 22 years, the country had gone from criminalising sexual activity between men to endorsing same-sex marriage. This result was warmly welcomed by gay rights activists around the world, but some raised concerns over the appropriateness of a referendum as a mechanism for protecting minority rights. One commentator referred to itas an “indignity,” noting that it was unseemly to put the civil rights of a historically oppressed minority to a popular vote. A proper appraisal of the Irish referendum, however, requires an appreciation its legal and social context. The referendum was held because relevant political actors believed that same-sex marriage required a constitutional amendment, which can only be accomplished by a referendum. The Irish referendum, therefore, cannot be understood as narrowly populist or majoritarian but instead should be seen as part of a consensus-building process required for constitutional amendment. While putting minority votes to a referendum came with costs—most significantly, the public dissection of the private lives of those who stood to benefit from the reform—the required consensus-building also had positive implications for members of the gay community. In short, it produced a much greater level of social acceptance than would likely have been achieved through either judicial or legislative recognition of a right to same-sex marriage. These benefits would likely not have arisen, however, if a referendum had been a choice on the part of political actors rather than a legal necessity. It is therefore unlikely that the Irish experience, whatever its merits, can be straightforwardly translated to other jurisdictions. Nevertheless, the Irish referendum campaign yields some lessons for other activist campaigns for same-sex marriage.In particular, I suggest that the storytelling of gay people—and the responses of their fellow citizens—may have been more significant than the articulation of more public values, such as equality.I begin with a brief account of how gay rights developed in Ireland prior to the movement for marriage equality. I then consider the legal arguments that bore on the questions of whether the Constitution either protected a right of same-sex couples to marry or precluded parliament from legislatively introducing same-sex marriage. I then explore the political moves that led to the 2015 referendum before assessing the key features of the referendum campaign, in both its public and private dimensions. I conclude by reviewing the appropriateness of putting minority right to a referendum, before identifying some lessons for political campaigners that arise from the Irish referendum campaign.
PUBLISHED
Keywords: Identities in Transformation; Making Ireland; Comparative Constitutional Law; Irish Constitutional Law; Identities in Transformation; Making Ireland; Comparative Constitutional Law; Irish Constitutional Law